(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
In order to reflect on the importance of instilling and maintaining values in individuals and their necessary reinforcement in professional training, an investigation is presented with a qualitative methodological approach, with a documentary design supported by an extensive bibliographic review. , which highlights the reflective position of the author in a hermeneutic process in which she inquires about axiology and its beginnings, as well as the importance of including it in professional training. For this, a conceptualization of the categories was made: university training, appearance of axiology and axiological training, with which a final conclusion was made that led to the issuance of some recommendations for feasible reception by academic institutions. The investigation reveals successful experiences and updates based on technology, which guide the incorporations in different educational instances.